2014
DOI: 10.1186/1745-6215-15-205
|View full text |Cite
|
Sign up to set email alerts
|

Peer volunteers in an integrative pain management program for frail older adults with chronic pain: study protocol for a randomized controlled trial

Abstract: BackgroundChronic pain is common among the older population. A literature review on pain management program showed that exercise, yoga, massage therapy, Tai Chi, and music therapy could significantly reduce pain. In spite of the proven benefits of pain management programs, these intervention programs were effective only in the short term, and older adults would resume their old habits. It has been suggested that interventions comprising some type of social support have great potential to increase the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The protocol has been published in details (Tse et al . ,b). A total of 32 nursing home residents participated in a 12‐week group‐based PV‐IPMP, with two 1‐h sessions per week on pain education given by peers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocol has been published in details (Tse et al . ,b). A total of 32 nursing home residents participated in a 12‐week group‐based PV‐IPMP, with two 1‐h sessions per week on pain education given by peers.…”
Section: Discussionmentioning
confidence: 99%
“…Another pilot study also demonstrated the effectiveness of an 8‐week play activities in reducing pain and loneliness, and enhancing happiness, functional mobility and life satisfaction among frail older adults (Tse et al . ,b). As the population ages, effective interventions should be explored which not only target on improving mobility and reducing pain, but also address loneliness among older adults in order to reduce frailty and improve quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The buddy peers support group introduced in this program may greatly increase social support which will be shown to be a key determinant of adherence to the exercise programs and create a commitment to achieve specified levels of physical activity ( 19 ). Therefore in this proposed study, peer-support groups with buddy members will be arranged in each daycare center.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, senior citizen volunteering is usually considered as a protective factor and health promoter. The positive health effects of volunteering include objective behaviours and conditions such as functional mobility, physical activity, the use of non-pharmacological pain-relieving methods (Tse et al 2014) and prevention of early mortality (Konrath et al 2012). These effects are also evident from a subjective perspective of wellbeing, volunteering can lead to: an improved emotional condition (Ho 2015;Morrow-Howell et al 2010), reduced stress (Greenfield -Marks 2004), a moderation of the impact of functional limitations on depression (Greenfield -Marks 2007), and the mitigation of the intensity of pain (Tse et al 2014).…”
Section: Introductionmentioning
confidence: 99%